Video Media to Improve the Learning Outcomes of Class II Students of SD Negeri 1 Candiwulan - Dwi Jayanti Ispiandari (Universitas Sebelas Maret, 2020)
The purpose of this research is to improve the learning outcomes of students on Theme 4 Clean and Healthy Living. The method for this research is classroom action research with the research subjects of class II students totaling 19 children at SD Negeri 1 Candiwulan. The instruments used are assessment of learning plans, assessment of the learning process, assessment of social attitudes, assessment of learners' skills, and assessment of knowledge. Achievement of percentage results obtained from cycles I, II, and III has increased. In the first cycle the percentage attainment was 73% with sufficient criteria, in the second cycle the percentage achievement was 80% with good criteria, and in the third cycle the percentage achievement was 88.4% with good criteria. So, it can be said that the use of video media can improve student learning outcomes in theme 4 of clean and healthy living.